Catalytic effect of MOF-derived transition metal catalyst FeCoS@C on hydrogen storage of magnesium. (1st March 2023) - Fu, Yaokun; Zhang, Lu; Li, Yuan; Guo, Sanyang; Yu, Zhichao; Wang, Wenfeng; Ren, Kailiang; Peng, Qiuming; Han, Shumin
Highlights: The FeCo@C and FeCoS@C catalysts are derived from ZIF-67. A heterogeneous C supported Mg2 Co, α-Fe, Co3 Fe7 and MgS catalyst system is formed. The MgH2 -FeCoS@C composite can absorb 4.56 wt% hydrogen within 900 s at 473 K. The initial dehydrogenation temperature of MgH2 -FeCoS@C composite is 550 K. The dehydrogenation activation energy of MgH2 is reduced to 91.9 kJ mol −1 . Abstract: The introduction of the heterogeneous catalysts with high activity can significantly improve hydrogen storage performance of MgH2, therefore, in this paper, we synthesize a carbon-supported transition metal compound, FeCoS@C derivative from ZIF-67, by utilizing the in situ formed C dispersive multiphase Mg2 Co, α-Fe, Co3 Fe7, and MgS to implement catalysis to MgH2 . Noteworthily, MgH2 -FeCoS@C rapidly absorbs 6.78 wt% H2 within 60 s at 573 K and can also absorb 4.56 wt% H2 in 900 s at 473 K. Besides, the addition of FeCoS@C results in decreasing of the initial dehydrogenation temperatures of MgH2 from 620 to 550 K. The dehydrogenation activation energy of MgH2 decreases from 160.7 to 91.9 kJ mol –1 . Studies show that the Mg2 Co, α-Fe, and Co3 Fe7 act as "hydrogen channels" to accelerate hydrogen transfer due to the presence of transition metals, and MgS with excellent catalytic effect formed from MgH2 -FeCoS@C provides a strong and stable catalytic effect. Besides, the carbon skeleton obtained by the carbonization of ZIF-67 not only serves as a dispersion for the multiphase catalytic system, but also provides more active sites for the catalysts. Our study shows that the multiphase and multiscale catalytic system provides an effective strategy for improving the hydrogen storage performance of MgH2 . Graphical abstract: Image, graphical abstract